The effectiveness of coping innovation interventions, reframing, and sleep hygiene in the adolescent aggregate of MTs Antasari Samarinda - Dini Andani Hasanah; Jumratul Amalia; Reza Wira Sanjaya; M. Bachtiar Safrudin (International Journal of Public Health Excellence (IJPHE), 2026)
Adolescents are a vulnerable age group that often experience various mental health problems, such as stress, bullying, and sleep pattern disturbances influenced by academic demands, social pressure, and the use of digital technology. These conditions may trigger maladaptive coping, risky health behaviors, and decreased adaptive capacity among adolescents. Preliminary assessment at MTs Antasari Samarinda showed that some adolescents experienced moderate to high levels of stress, were at risk of bullying, and had sleep pattern disturbances with ineffective coping patterns. This study aims to analyze the effectiveness of innovative interventions involving coping strategies, reframing techniques, and sleep hygiene among adolescents at MTs Antasari Samarinda. The method used was a case study with a community nursing care approach that included assessment, diagnosis, planning, implementation, and evaluation. The assessment was conducted using several instruments, namely the Perceived Stress Scale (PSS-10), Bullying and Cyberbullying Scale for Adolescents (BCS-A), Brief-COPE, and Pittsburgh Sleep Quality Index (PSQI), along with interviews and observations. The interventions included training in problem-focused coping and emotion-focused coping, reframing techniques through structured counseling sessions, as well as education and implementation of sleep hygiene practices. The results showed an improvement in adolescents’ ability to manage emotions and solve problems adaptively, a reduction in bullying tendencies and negative thought patterns, and improved sleep quality after the intervention. These findings indicate that innovative coping, reframing, and sleep hygiene interventions are effective in improving adolescents’ mental health and adaptive behaviors, as well as supporting community nursing care practices in the school environment.